Transformasi Pembelajaran Fikih dengan Metode Simulasi : Studi pada Siswa Kelas IV MI Nurul Huda Manyarejo - Leny Nofianti (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This study aims to determine the efforts of teachers in increasing students' interest in learning the subject of fiqh through the application of simulation methods in class IV MI Nurul Huda Manyarejo. This study uses a descriptive qualitative approach with a focus on the implementation of simulation methods in the learning process. The formulation of the problem in this study includes: (1) what are the steps in implementing the simulation method in increasing students' interest in learning, (2) how is the quality of the simulation method in fiqh lessons, and (3) what are the supporting and inhibiting factors in implementing the method. The data analysis technique uses an interactive analysis model which includes the stages of data collection, data reduction, data presentation, and drawing conclusions. The research procedure was carried out through four stages, namely pre-field, data collection in the field, data analysis, and preparation of research reports. The results of the study showed that the simulation method was able to create a more enjoyable and less boring learning atmosphere, thus increasing the enthusiasm and enthusiasm of students, especially when studying fiqh material such as the zakat chapter. The teacher succeeded in arousing students' interest in learning through an interactive and applicable approach. Thus, the simulation method is considered an effective learning strategy in increasing students' interest in learning the subject of fiqh.